The Effect of Discount Flash Sale on Online Impulsive Buying of Mercubaktijaya University Students at Shopee Marketplace - M. Zai, Yovita Yulia; Hafiza, Siti Nur; Nur, Rahmi M (Journal La Bisecoman, 2025)
The development of digital technology is currently triggering an online shopping model characterized by the development of marketplaces and online marketing strategies to attract consumer interest. This study aims to determine whether there is an influence between the marketing strategy of the Shopee discount flash sale marketplace on online impulsive buying. This research is a quantitative study where the sample determination uses Non-Probability Sampling with Purposive Sampling technique to Mercubaktijaya University Padang students. Data was obtained through a questionnaire distributed with a sample size of 100 respondents. The analysis technique uses multiple linear regression and hypothesis testing using the F test and t test. The data was processed using SPSS (Statistical Package for the Social Sciences) software version 26. The results showed that the correlation between the discount flash sale variable and online impulsive buying showed a positive correlation relationship with a value of 0.546 with a correlation strength level of moderate. There is an influence between the discount flash sale variable on online impulsive buying. This can be seen in the value of t count) (2.128) > t table (1.98422), and the significance value (0.036) <0.05. When viewed from the coefficient beta value, the discount flash sale variable has a contribution in online impulsive buying of 0.270 which shows a unidirectional relationship between the discount flash sale variable and online impulsive buying, which means that if the activity of the discount flash sale increases, it will make impulsive buying activity on Shopee increase as well.